(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
Outbreaks of epidemics and pandemics have had devastating effects on human livelihood with enduring scare on the socio-economic foundations of the society. This study sought to examine the impact of “Covid-19” pandemic on the Nigerian tourism and hospitality industry.The exploratory methodology was adopted for the study and it was found that the tourism and hospitality industry remains one of the worst affected industries by the novel Corona virus pandemic in Nigeria.Aside the health crisis that came with the pandemic, the study also found that as Nigerian government resorted to nonpharmaceutical measures such as community lock-down, social distancing,restriction of gatherings, closure of borders and airspace, tourism activities declined severely; resulting to a near-collapse of the Nigerian tourism and hospitality industry.Thus the study proposed robust electronic operations system to boost the industry’s performance or at least sustain it from further strain from the covid-19 pandemic. Tourist sites and hospitality operations managers are advised to develop an eoperations system that best suit the unique need of their business, as this technique has recorded great success in the banking,telecommunications, logistics, educational, media and entertainment industries. The study also advised Nigerian government to provide timely support to cushion the effect of Covid-19 in the industry.